2015
DOI: 10.1124/mol.115.098913
|View full text |Cite|
|
Sign up to set email alerts
|

Desformylflustrabromine (dFBr) and [3H]dFBr-Labeled Binding Sites in a Nicotinic Acetylcholine Receptor

Abstract: Desformylflustrabromine (dFBr) is a positive allosteric modulator (PAM) of a4b2 and a2b2 nAChRs that, at concentrations .1 mM, also inhibits these receptors and a7 nAChRs. However, its interactions with muscle-type nAChRs have not been characterized, and the locations of its binding site(s) in any nAChR are not known. We report here that dFBr inhibits human muscle (ab«d)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Mutagenesis studies using an EC 75 concentration of ACh suggested that dFBr binds at extracellular β2/β2 and β2/α4 sites (Weltzin and Schulte, ). These sites are also supported by photoaffinity labelling of Torpedo nAChRs (Hamouda et al , ). Another study using mutagenesis, SCAM and docking indicates that dFBr binds at the interface between the extracellular and transmembrane domains when testing its PAM effect at an EC 10 concentration of ACh (Alcania et al , ).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Mutagenesis studies using an EC 75 concentration of ACh suggested that dFBr binds at extracellular β2/β2 and β2/α4 sites (Weltzin and Schulte, ). These sites are also supported by photoaffinity labelling of Torpedo nAChRs (Hamouda et al , ). Another study using mutagenesis, SCAM and docking indicates that dFBr binds at the interface between the extracellular and transmembrane domains when testing its PAM effect at an EC 10 concentration of ACh (Alcania et al , ).…”
Section: Introductionmentioning
confidence: 84%
“…(R)‐7‐bromo‐N‐(piperidin‐3‐yl)benzo[b]thiophene‐2‐carboxamide (Br‐PBTC) acts from the extracellular C‐terminus of α2 or α4 in association with nearby parts of the α subunit (Wang et al , ). Desformylflustrabromine (dFBr) was initially reported to act at the extracellular domain (Weltzin and Schulte, ; Hamouda et al , ; Weltzin and Schulte, ), but has recently been reported to act in the transmembrane domain near the C‐tail of α4 near where Br‐PBTC and estradiol act (Alcania et al , ). Type II PAMs for heteromeric nAChRs that act directly at or close to the desensitization gate may be found.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoaffinity labeling identifies amino acid residues within the protein structure that are in direct contact with a bound drug and differentiates them from amino acids not contributing to the binding site but important for drug action, which can be identified by mutational analyses. Even though CMPI bound with .30-fold higher affinity in the Torpedo nAChR ion channel than in the transmitter binding sites, 55 in the g subunit, suggests that CMPI binds preferentially to the ACh binding site at the a-g interface, as is seen for d-tubocurarine, the classic muscle-type nAChR competitive antagonist, which photolabels the same amino acids in the ACh binding site as CMPI (Chiara and Cohen, 1997;Chiara et al, 1999 (Chiara and Cohen, 1997;Nirthanan et al, 2005;Srivastava et al, 2009 (Hamouda et al, 2013(Hamouda et al, , 2015 , which indicates that CMPI does not bind to the dFBr/ physostigmine/galanthamine allosteric sites in the ECD at the a/g subunit interface near the entry of the ACh binding site or in the vestibule of the ion channel.…”
Section: Discussionmentioning
confidence: 99%